Stretching single fibrin fibers hampers their lysis. (15th September 2017) - Li, Wei; Lucioni, Tomas; Li, Rongzhong; Bonin, Keith; Cho, Samuel S.; Guthold, Martin
Graphical abstract: Fibrin fibers thicken and elongate after lysis. Stretching fibrin fibers hampers lysis of uncrosslinked (red dots) and crosslinked (blue crosses) fibers. Strain may be a mechanobiological factor that regulates blood clot dissolution (fibrinolysis) at the single fiber level. Abstract: Blood clots, whose main structural component is a mesh of microscopic fibrin fibers, experience mechanical strain from blood flow, clot retraction and interactions with platelets and other cells. We developed a transparent, striated and highly stretchable substrate made from fugitive glue (a styrenic block copolymer) to investigate how mechanical strain affects lysis of single, suspended fibrin fibers. In this suspended fiber assay, lysis manifested itself by fiber elongation, thickening (disassembly), fraying and collapse. Stretching single fibrin fibers significantly hampered their lysis. This effect was seen in uncrosslinked and crosslinked fibers. Crosslinking (without stretching) also hampered single fiber lysis. Our data suggest that strain is a novel mechanosensitive factor that regulates blood clot dissolution (fibrinolysis) at the single fiber level. At the molecular level of single fibrin molecules, strain may distort, or hinder access to, plasmin cleavage sites and thereby hamper lysis. Statement of significance: Fibrin fibers are the major structural component of a blood clot. We developed a highly stretchable substrate made from fugitive glue and a suspended fibrin fiber lysis assay to investigate the effect of stretching on single fibrin fibers lysis. The key findings from our experiments are: 1) Fibers thicken and elongate upon lysis; 2) stretching strongly reduces lysis; 3) this effect is more pronounced for uncrosslinked fibers; and 4) stretching fibers has a similar effect on reducing lysis as crosslinking fibers. At the molecular level, strain may distort plasmin cleavage sites, or restrict access to those sites. Our results suggest that strain may be a novel mechanobiological factor that regulates fibrinolysis.